Feeding soy protein concentrates with low or high isoflavone decreases liver inflammation by reducing lipopolysaccharide translocation - Li, Wei; Hakkak, Reza (Frontiers in Nutrition, 2023)
Lipopolysaccharide (LPS) translocation and inflammation contribute to the increased risk of chronic diseases, including non-alcoholic fatty liver disease (NAFLD), associated with obesity. Previously, we reported that feeding soy protein with high or low (negligible) isoflavone reduces liver steatosis in obese Zucker rats, and the reduced steatosis is accompanied by decreased serum C-reactive protein levels. The current study investigated the effect of feeding soy protein concentrate (SPC) with high or low isoflavone (HIF or LIF) on liver inflammation and LPS translocation in obese Zucker rats. Six-week-old male lean (L, n = 21) and obese (O, n = 21) Zucker rats were fed casein control, SPC-LIF, or SPC-HIF diets for 18 weeks. At the end of 18 weeks, the expression levels of tumor necrosis factor-α (TNF-α), monocyte chemoattractant protein-1 (MCP-1), inducible nitric oxide synthase (iNOS), arginase 1 (ARG1), lipopolysaccharide binding protein (LBP), myeloperoxidase (MPO), and sterol regulatory element-binding protein 1 (SREBP-1) were significantly higher in obese rats compared to lean rats. Compared to the casein control diet, both the SPC-LIF and SPC-HIF diets significantly decreased TNF-α, MCP-1, iNOS, and LBP expression in obese rats, which is accompanied by significantly less LPS staining in liver slides from SPC-LIF-and SPC-HIF-fed obese rats compared to the casein control diet-fed obese rats. Taken together, the SPC-LIF and SPC-HIF diets attenuated liver inflammation in obese Zucker rats, likely by decreasing LPS translocation.